KAZAKHSTAN IN CHINA'S EURASIAN STRATEGY: ENERGY, CONNECTIVITY, AND THE BELT AND ROAD INITIATIVE (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article traces the development of China–Kazakhstan relations from Kazakhstan's independence in 1991 to the present day, focusing on the political, economic, security, and geopolitical dimensions of their bilateral partnership. Using a historical and qualitative approach, the study follows how the relationship evolved from the initial establishment of diplomatic ties into what is now a comprehensive strategic partnership, marked by deepening cooperation in energy, transportation, trade, and regional security. Special attention is paid to Kazakhstan's strategic role within China's Belt and Road Initiative (BRI), the buildout of cross-border infrastructure and energy corridors, and the increasing weight of bilateral trade and investment in the relationship. The article also considers how multilateral mechanisms — particularly the Shanghai Cooperation Organization (SCO) — have contributed to building mutual trust and reinforcing regional stability.
Keywords: China; Kazakhstan; Central Asia; Belt and Road Initiative (BRI); Strategic Partnership; Energy Cooperation; Shanghai Cooperation Organization (SCO); Eurasian Connectivity; Foreign Policy; Xinjiang; Regional Security; Bilateral Trade.